Binder-free three-dimensional interconnected CuV2O5·nH2O nests as cathodes for high-loading aqueous zinc-ion batteries. Issue 4 (21st January 2022) - Ren, Jie; Hong, Ping; Ran, Yan; Chen, Yunhua; Xiao, Xuechun; Wang, Yude
Abstract : Binder-free three-dimensional interconnected CuV2 O5 · n H2 O nests as cathodes for high-loading aqueous zinc-ion batteries show an impressive enhancement of the performance including the rate performance and cycling stability. Abstract : In large-scale energy storage applications, aqueous zinc ion batteries (ZIBs) with low cost, safety, high theoretical capacity, and environmentally friendly nature have wide application prospects. In the reported cathode materials, the mass loading of cathodes is generally less than 3 mg cm −2, which makes it hard to meet the requirements of industrial production. To fabricate high-loading ZIB cathodes, a copper ion-intercalated hydrated vanadium dioxide on carbon cloth (Cu0.18 V2 O5 ·0.72H2 O@CC) without a binder was developed. The cathode has a unique three-dimensional interconnected nest structure with high loading (∼7 mg cm −2 ), high capacity (223.4 mA h g −1 at 1 A g −1 current density), and long cycle performance over 2000 cycles. Compared with the VOH@CC cathode, Cu 2+ intercalation makes the VOH cathode have a better capacitance response and faster diffusion rate, which means better rate performance and cycling stability and provides a feasible design scheme for the production of industrial-grade ZIBs.